2020
DOI: 10.7554/elife.58496
|View full text |Cite
|
Sign up to set email alerts
|

International authorship and collaboration across bioRxiv preprints

Abstract: Preprints are becoming well established in the life sciences, but relatively little is known about the demographics of the researchers who post preprints and those who do not, or about the collaborations between preprint authors. Here, based on an analysis of 67,885 preprints posted on bioRxiv, we find that some countries, notably the United States and the United Kingdom, are overrepresented on bioRxiv relative to their overall scientific output, while other countries (including China, Russia, and Turkey) show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 44 publications
4
26
0
3
Order By: Relevance
“…Although the data is not large, we can deduce that international collaborators drive the adoption of preprints. This trend has been observed in some African countries, including Kenya (Abdill et al, 2020 ). Overall, based on the 2018 data we obtained from the BioRXiv preprint server, one of the largest available, Kenya is leading Africa in preprint publications ( Figure 4 ).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Although the data is not large, we can deduce that international collaborators drive the adoption of preprints. This trend has been observed in some African countries, including Kenya (Abdill et al, 2020 ). Overall, based on the 2018 data we obtained from the BioRXiv preprint server, one of the largest available, Kenya is leading Africa in preprint publications ( Figure 4 ).…”
Section: Resultssupporting
confidence: 60%
“…Overall, based on the 2018 data we obtained from the BioRXiv preprint server, one of the largest available, Kenya is leading Africa in preprint publications ( Figure 4 ). However, as of 2020, South Africa and Ethiopia were leading in Africa in the number of preprints deposited in BioRXiv (Abdill et al, 2020 ). The growth in adoption of preprints by South African and Ethiopian researchers may be partly explained by the increased uptake of the publisher-driven opt-in options to post preprints in BioRXiv (PLOS, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, we matched 54,289 preprints to a country (72.8%); for COVID-19 preprints alone, 6,692 preprints (65.4%) were matched to a country. Note that a similar, albeit more sophisticated method of matching bioRxiv affiliation information with the ROR API service was recently documented by Abdill and colleagues [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, adoption of preprints so far has been mostly driven by researchers in North America and Europe. A recent study of bioRxiv content concluded that countries such as the United States and the United Kingdom are overrepresented on bioRxiv relative to their overall scientific output (Abdill et al, 2020) . This is probably not a surprising trend; the researchers more comfortable posting a preprint are likely to be those with more established recognition and positions (N. C. , and the countries with a high preprint representation overlap with those where more funders and national agencies have expressed support for preprints.…”
Section: Disparities In Adoptionmentioning
confidence: 99%